Modern Mimarlığın Süreklilikleri 20.yüzyıl Modernizmi İçin Ortak Bir Zemin Oluşturma Çalışması - Yırtıcı, Hakkı (Fen Bilimleri Enstitüsü, 1996)
1960larla beraber siyasetten ekonomiye, kültürden sanata hayatın her alanında modem toplumun kültürel mantığından belli bir kopuşun ifadesi olarak postmodernizm terimi telafuz edilmeye başlandı. 20 yıllık bir postmodemizm deneyiminin ardından ise modernizmin yeniden dirildiği ya da aslında bir kopmanın olmadığı, modernlik ve modemizmin halen varlığım koruduğu yönündeki itirazlar gerek toplumsal alanda, gerekse mimarlık disiplini içinde önemli bir yer tutmaya başladı. Bu çalışma da, farklı alanlarda dile getirilen ve temel olarak postmodernizmin öne sürdüğü kopuşun bir yanılsama olduğu ve halen 17. yüzyıldan beri devam eden ve modernleşme olarak adlandırılan bir sürecin içinde olunduğu argümanına dayanmaktadır. Ancak ortadaki sorunu kabaca modemizm / postmodemizm karşıtlığı olarak algılamak, her geçen gün daha karmaşık bir görünüm kazanan modem toplumun doğasını da gözardı etmek demektir. Postmodemizm, modernlik ve modemizm üzerine tekrar düşünmek için firsat yaratmıştır. Bu nedenle postmodernizm, modernizmin karşıtı olarak alınıp, reddedilmek yerine; içinden geçilmeli ve yüzyıl sonuna gelinen bir dönemde, 20. yüzyıla özgü bir modernist bilinci kurabilmek için itici güç olarak değerlendirilmelidir. Bu çalışma, benzer çalışmalarda olduğu gibi bir giriş - gelişme - sonuç bölümlerinden oluşmamaktadır. Kendi içinde bağımsız üç bölüm bulunmaktadır. Her bölüm tek başına ve ayrı okumalara olanak vermekle beraber, son kertede, yukarıda öne sürülen argümanın farklı boyutlarını ele aldığından bir bütünlük içerisindedirler. İlk bölüm olan "Postmodemite - Kopuş EfektTnde, bugüne postmodernizm perspektifinden bakıldı. Postmodernizmin ne olduğu, içinde barındırdığı farklı fraksiyonların konumlarım belirlemek ve bunlar arasındaki modernist unsurları bulup, ortaya çıkarmak bu bölümün ana eksenini oluşturdu. "Modernite - Gerçek Kopuş" bölümünde ise bugün, sadece kendi içinde kalınarak değil 17. yüzyıldan beri süregelen ve 20. yüzyılla beraber daha da keskinleşen bir sürecin parçası olarak değerlendirildi. Bu bölümün ana eksenim de, postmodernliğin aslında modernlik denilen bütünün bir parçası olduğunun ve modernlik tarafından nasıl kuşatıldığının gösterilmesi oluşturdu. Son bölüm olan "Modern Mimarlığın Sürekliliklerinde ise diğer iki bölümden farklı olarak, mimarlık disiplini içinden konuşarak, mesleğin kendine özgü süreklilikleri gösterilmeye çalışıldı. Bu bölümde, mimarlığın asıl ürünü olan bina temel alınarak, modem mimarlığın ortak karakteristikleri ortaya kondu.

Since the 1960s the term postmodernism began to be used to define the break from the cultural logic of the modem society of the variety of spheres from economics to culture and art. But following the postmodernist experience, which lasted for about 20 years, various objections were heard both in the cultural sphere and within the discipline of architecture, claiming that what happened was merely the revival of the modernism or there has never been a real break and that modernity and modernism continue to be a current force. This study too is based on the argument that the alleged postmodernist break in differenr disciplines is illusionary and that we are still within the modernist experience continuing since the 17th century. To pose the problem as opposition of modernism and postmodernism however ignores the nature of the modern society which is becoming more and more complex each day. Postmodernism has created the chance of reewaluating modernity and modernism. Therefore postmodernism should not be negated as something opposed to modernism: rather, in a period marking the end of the century, it should be taken as an impetus for creating a modernist consciousness which is characteristically valid for the 20th centurv. This study isn't composed of conventional chapters, namely an introduction, a main study and a conclusion. Instead, it is composed of three independent chapters. Althought each chapter allows separate and independent readings, the three of them together constitute a whole in the final analysis, since they deal with different aspects of the argument mentioned above. In the first chapter entitled l"Postmodernity - The Break Effect", the present situation is evaluated from the perspective of postmodernism. Definition of postmodernism o fthe different factions within it and the detection of the modernist elements among them constituted the main axis of this chapter. In the chapter entitled "Modernity - The Real Break" the present is taken not as something on its own, but as result of a-a process going on since the 17th century, a process which has become more acute in the 20th century. What constitues the main axis here is that the postmodernism is in fact a part of the whole called modernism and that it is encircledr by it. The last chapter entitled "The Continuities of The Modern Architecture", unlike the other two chapters, speaks from within the discipline of arcitecture and tries to show the continuities that the profession has of its own. In this chapter, focusing on the building, which is the basic architectural artifact, the common characteristics of 20th centurv architecture is discussed. Postmodernity - The Break Effect Today a discussion on modernity and modernism inevitably has to settle accounts with postmodernism. Postmodernism provides the basic means for conceptualizing the world we live today. More significantly, since it poses the question of modernity and modernism and since it manifests itself as something in relation to modernism, modernism and postmodernism are part of a single problematics. The problematics of postmodernism is in fact something too complex, while the term postmodernism is encompassed a whole range of spheres from economics to politics, from culture to art, it became an ambigjous term due to its being used to describe such very diffemt practices. The term postmodernism was first used in 1950 by Irwing Howe and Harry Levin to describe the exhaustion of literary modernism. But it gained its present meaning after a consciousness that emerged in the 1970s, a consciousness that thigs are coming to an end. By using the prefix "post-" it separated itself from the modern, put a distance between itself and the modern and fulfilled itself with this distance. Then what is postmodernism? Among the numerous definitions the most comprehensive is the one by Jameson. According to Jameson, postmodernism is not a movement or a style on its own, rather it is a culturaly dominant element which influences and creates a pressure on all the different movements and styles in a particular historical period. Here postmodernism is evaluated as a social and cultural formation which emerged as a result of the crises of the capitalist wellfare state. There are a lot of cases where this formation can be observed concretely: Giving up the demand for universality/ approval of the particular and the local/ pluralism/ the fading away of the boundaries between different fields/ the disappearance of the distance between reality and appearance, between signifier and the signified/ the negation of the representation/ acceptance of unrepresentability rather than the unknowabiJity/ revival of the discourse on the Other/ the disappearance of the center/ superficiality/ the craze of consumption/ blurring the distinction between the high culture and mass culture/ the preoccupation of the cultural language with categories of space rather than those of time/ the glorification of populism/ negation of universal styles in architecture and art. After all these evaluations, here are the images we still restore: Break, giving up, acception, dissolution, dispersion and fragmentation. There is a negative stress in all of them. Underlying this negative evaluation is the theme of the breaking away from the cultural logic of the modem society. But whenever the consciousness identifies postmodernist with anti-modernism, the equation closes upon itself and falls short in evaluating the present. The free one from this negativity one should show the different factions within postmodernism itself, giving special emphasis to those elements indicating the traces of a modern consiousness. To study different factions within postmodernism, one might begin with Norberg - Schulz. According to Norberg-Schulz postmodernism is Janus faced; one face looks back and tries to recapture the language of meaningful forms, the other looks in to the future, into the nothingness and gets lost amidst forms. Norberg-Schulz claims that the nihilist face of postmodernism, looking into the future, represents the Late Modern point of view; these are the last efforts of Utopian modernism he says. The other face he calls "pure postmodernism"; its main purpose is to bring meaning back. The positive stress here is on that face of postmodernism looking back. Hal Foster, too, in his collection entitled "Anti Aesthetics" divides postmodernism into two factions, but this assessment is just the opposite of that by Norberg-Schulz. He evaluates postmodernism under two headings, one being reactionary postmodernism, the other post modernism of resistance. While reactionary postmodernism takes shelter in the therapeutic virtues of tradition, the postmodernism of resistance attempts a critical deconstruction of all traditionsi without ever returning to itself. Generary speaking, the postmodernism of resistance, instead of abusing the cultural codes, investigates problems, unveiling rather than covering up social an d political and political relations. The detailed definitition is the one by Jameson. He lists four main positions in postmodernism: pro-postmodern/anti-modern; anti-postmodern/anti-modem; anti- postmodern/pro-modem. Within these four basic positions, the one described as "pro- postmodern/pro-modem" involves the continuities between postmodernism and modernism. The most important figure within the pro-postmodern/pro-modem position is Lyotard. According to Lyotard, postmodern is the embryonic form of the modem. He tries to revive the modernist spirit within the postmodern and tries to show the common grounds with the early 20th century avat-garde attitudes. Modernity-The Real Break In this chaptre modernity is to be taken the body of experiences that realize themselves in situations mentioned above, without going into the philosophical institutional socio economic, technological and cultural aspects. Modernity is the general term used to describe the forms of social life and organisations emmerged in the 17th century europe and which than expanded to the whole world. The characteristics that make modernity really significant is the fact that it established a system which is radically different from the previous traditional systems, a system uniquely ite own. This uniqueness implies a discontinuity from the traditinal systems. According to Giddens, this discontinuities are the speed of change, the sperer of change and the nature of modern institutions. VI This discontinuities are directly related to a series of processes called modernization. These processes include: The developments in physical sciences, industrialization, demographic uprootedness, urbanization, the expansion of the media, the gaining power of the nation states, mass movements and capitalist world market. Capitalist world market distinguishes itself from all other in that it creates a void in which all the other processes can operate. According to Marx the key word in understanding the modernity is capitalism. To discover the reasons behind the unstable an dynamic character of modem society, one should look at the capitalist economic order. In the capitalist economy there is a strong tendency to use surplus value for increasing the productivity. This process is not only creative but also inevitably destructive. The present working methods are replaced as soon as new methods are discovered. The new may become old just ovemigth. The ambivalent nature of capitalist economy is not limited to economic phenomena. This ambiguity in economics, the dialectics of creating and destroying inevitably influences the other spheres of the modern world, the social and institutional patterns, dairy life and cultural systems. Now, keeping this picture in mind, one can talk about a modern consciousness which is the result of living in the modern world while feeling all the tumults that modernization brings together with it. Modem consciousness is primarily related to time and its momentary. It tries to define the present by refering to it alone. Modem consciousness has fight against the doubt and uprootedness that is a result of the unrepresentability of the world we live in, its constant movement and the unsufficiency of form and contents inherited from the past. To be modem forces one to destroy all is around, to be foreign, to live in a temporary world where everything is falling apart. There are no meanings or values which can serve as a reference point. There is no room for memory. This modem consciousness ironically gives rise to myth of "lost paradise". One needs a defense mecanism against temporariness and uprootedness that modern world offers. Thus the tradition that was left behind while the modem world was built, returns as one of the primary needs of modem man. The return of tradition points to a modem situation; but this time tire tradition is radically different from the pre-modern tradition. The "old" tradition needed nothing to compare itself with, needed noother reference point; the "new" one is surrounded by modernity and it can define itself only through an Other. This Other is modernism itself. Tradition that is surrounded by modernity is new rather than old; it is part of the modem situation. It not borrowed from the old some people believe, it belongs totaly to the present. It fictive; constructed voluntarily in the present as result of the selection from mass of material history provides. Keeping all these in mind, now should go back to the issue of postmodernism. Now we can see modernism with the concepts of modernism. Whene one works throught the uprootednes and temporariness which are the characteristics of 20th century and modernity, throught the crises that follow one other and that constanatiy reproduce themselves, throught the numerous "-isms" and the pluralism, this gives rise to, the VII break that postmodernism claims for itself and the distinction between postmodernism and modernism fades away, loosing its significance. Postmodernism then is not something that expresses abreak from the cultural logic of modem society, rather a permanent part of crises of modernity. The posing of postmodernism itself - especially in cultural realm, in art and architecture- as an updating of past and as something radically different and contrary to modernity, becomes thenthe modern expression of the need to acquire a history and a tradition, a need necessitated by the modem consciousness. The Continuities of Modern Architecture In this chapter three buildings are studied, namely LeCorbusier's Apartment Blocks in Marsilia, Wright's Falling Water House and Rietveld's Schroder House. But this will not be an exclusive study of these bulidings, since numerous other buildings are refered to establish the continuities between the beginning and the end of the 20th century. It will be sufficient to study the continuities between the buildings without going into their details. 1. With rise of the modem world, social consensus on the building was destroyed. Architecture was no longer able to meet various needs of society by staing within tradition. From then on architecture needed to be reconstructed as a rational act each time. This is inevitably true both for modem architecture which chose to start from a zero degree and for historicist positions claiming to rely on history and tradition. 2. There is a common sensibility' behind all the positions within the 20th century architecture. The motive behind them all is to act in a world of constant change, a world which is a destructive dynamics, a world the cognitive map of which can not be drawn, a world where all meaning has been exhausted. This motive creates a common platform for all the 20th century movements, while the different attitudes and reactions constitute the distinctions. 3. The pre-modem was a place where there was no contradiction between the subject and the object, where all the objects were believed providencial evidences. With birth of the philosopy of Enlightment the world was stripped of its spritual identity, being demystified. The objects became isolated entities in need of investigation, waiting to be discovered. All of the architectural movements in the 20th century accepted object itself as a problem to be solved. To explain the object, one has to transform into a abstract entity or else one has to dissect and analyze it. From this respect, the distance between Rohe's skyscrapers composed of single rectangular prisms and the deconstructrvist experiments is less then it seems to be.
The Continuties Of Modern Architecture
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1996
Keywords: Modernizm; Modernism